Plans, Open Future and the Prospects for a Good Life - Steinfath, Holmer (Ethical theory and moral practice, 2024)
How we live our lives depends on how we relate to our past, present and future. The article focusses on the relation to our future. The target of my critique is a "planning conception" that imagines the future as a realm that we can rationally plan and form in light of our ends. In the first section I present an outline of the planning conception, building on Bratman’s planning theory and Rawls’ idea of a life plan. The second section highlights the attractions of the planning conception. I argue that this conception offers a prima facie intriguing view of the temporality of human life. It promises a life in which we can control the passage of time. The third section reveals severe limitations of the planning conception. I question the claim that plans are central to our self-understanding and to a good life. The planning conception tends to distort the temporality of human life with respect to past, present and future. Given this diagnosis, I sketch an alternative in the last section of the paper. I explore the temporal specifics of ways of understanding oneself as a person and argue that both the formation and the very form of these ‘ways of being’ do not follow the logic of planning.